URGENSITAS PENGUATAN ETIKA PROFESI HAKIM - Athari Farhani; Faiqah Nur Azizah; Nur Kholifah (Ikatan Hakim Indonesia (IKAHI), 2024)
The judge as the main element in the court places his profession as a representative of God, because the judge's job is to determine law and justice in society, so the responsibility he bears is very heavy but noble. Therefore, the profession of judges has such great power, that judges are required to balance an attitude that is full of responsibility to conscience and ethical values ​​towards their profession. However, if you look at the current reality, there has been a decline in the quality of judges not only in their decisions but also in regards to a decrease in the moral aspect. Strengthening ethics in the profession of judges is a necessity and obligation for state administrators because ethics is the main corridor for judges in carrying out their duties so that they continue to carry out their profession in a professional manner without putting aside the values ​​of honesty and morality. This is an effort to realize fair law enforcement. The research method used in this study is a normative method with a conceptual approach and a statutory approach. The results of this study are that judges must be able to embody ethical and moral values ​​as formulated in the code of ethics for the profession of judges, namely by exploring the sense of justice held by society. With an ethical and moral foundation through the professional code of ethics of judges, judges will realize fair law enforcement.